Activities of Some Medicinal Plants on the Proliferation and Invasion of Brain Tumor Cell Lines. (27th August 2020) - Ngulde, Saidu I.; Sandabe, Umar K.; Abounader, Roger; Zhang, Ying; Hussaini, Isa M.
Abstract : Cancer is a debilitating disease that is on the increase in both developed and developing countries. Anticancer drugs are often expensive, have narrow spectrum of activities, and are associated with toxicities and side effects such as myelosuppression, immunosuppression, gastrointestinal disturbance, alopecia, skin toxicity, and hepatotoxicity. Plants have been the major source of anticancer drugs both in orthodox and traditional medicine. Many of the plants claimed by the traditional medicine practitioners (TMPs) to be effective in the treatment of cancer are yet to be evaluated scientifically. In this work, five medicinal plants used by TMPs in Borno State, Nigeria, were tested against two brain tumor cell lines. Ethanol extracts of Securidaca longepedunculata, Andira inermis subsp. rooseveltii, Annona senegalensis, Carissa edulis, and Parinari polyandra were used. U87 and U231 brain tumor cell lines were used for proliferation assay, U251 cell line was used for the invasion assay in collagen V coated inserts, and U87 cell line was used for the western blot detection of cleaved Poly-ADP-Ribose-Polymerase (PARP). The result revealed that all tested extracts significantly (p < 0.05 ) inhibited the proliferation of U87 and U231 cell lines with the respective IC50 values ranging between 8 and 20 μ g/ml for S. longepedunculata and 100 and 90 μ g/ml for P. polyandra . The five extracts significantly (p < 0.05 ) inhibited the invasion of U251 cell line at the concentration of 10 μ g/ml ( S. longepedunculata ), 20 μ g/ml ( A. inermis ), 50 μ g/ml ( A. senegalensis ), 50 μ g/ml ( C. edulis ), and 50 μ g/ml ( P. polyandra ). Securidaca longepedunculata extract induced the cleavage of PARP. It was concluded that these medicinal plants have antiproliferative and anti-invasive activities and possess good prospects as source of anticancer agents especially S. longepedunculata which induced apoptosis in U87 cell line.